2020
DOI: 10.3390/ma13204503
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Process-Induced Deformation for Composite Parts Considering Tool-Part Interaction

Abstract: Residual stresses are generated by tool-part interaction due to the large difference in the coefficients of thermal expansion (CTE) between the tool and the composite part, resulting in more process-induced part deformation. In this paper, a 3-D numerical model considering the influence of tool-part interaction is proposed to predict the deformation in complex-shape composite parts. In this numerical model, the existing path-dependent model is improved to consider the effect of tool-part interaction by adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As shown in Table 2, regardless of the curing conditions, the spring value of thin composite parts is greater than the corresponding thick composite parts. Furthermore, Qiao et al 71 quantitatively analyzed the influence of component structural parameters on the spring-in angle. The results show that with the increase of part thickness, the spring angle caused by chemical shrinkage and tool-part interaction decreases, while the spring angle caused by thermal shrinkage almost stays the same.…”
Section: Part Geometry Optimizationmentioning
confidence: 99%
“…As shown in Table 2, regardless of the curing conditions, the spring value of thin composite parts is greater than the corresponding thick composite parts. Furthermore, Qiao et al 71 quantitatively analyzed the influence of component structural parameters on the spring-in angle. The results show that with the increase of part thickness, the spring angle caused by chemical shrinkage and tool-part interaction decreases, while the spring angle caused by thermal shrinkage almost stays the same.…”
Section: Part Geometry Optimizationmentioning
confidence: 99%
“…Among these conditions, the temperature gradient and tool-part interaction play key roles in the composite deformation after demolding. 8,9,41,42 In contrast to ideal uniform cooling, one-sided cooling or outside-to-inside cooling, which is a more common scenario in the actual thermoforming process of thermoplastic composites, will generate temperature gradients through the thickness of the material. In turn, this will alter the residual stresses as well as the deformation of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a tool-part interfacial layer composed of the mold, composite, and demolding sheet is typically employed to accurately simulate the shear stress transmission between the mold and composite in FE simulations of the thermoforming process. 9,42 Previous studies have demonstrated that the simulation results become more precise when this interfacial layer is included in the FE model for composite laminates, 9,43 C-shaped, and U-shaped composite parts [42][43][44] . In summary, complex thermoforming conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [ 20 ] adopted a finite element-based cure simulation to forecast the curing behavior and material properties of thermoset fabrics and investigated the effect of fabric parameters on the deformation induced by the curing process of plain woven composite structures. Qiao et al [ 21 ] studied the curing deformation of complex-shape composite parts using a 3D numerical model considering the influence of tool–part interaction. Kawagoe et al [ 22 ] predicted process-induced deformation of laminates due to curing and thermal shrinkage using a multi-scale model consisting of microscopic and macroscopic finite element analysis, taking into account material and geometric nonlinearities.…”
Section: Introductionmentioning
confidence: 99%